PERLINDUNGAN HUKUM TERHADAP AHLI YANG MEMBERIKAN KETERANGAN DI PENGADILAN - Dayu Dawana; Erdianto Effendi; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Protection is all efforts to fulfill rights and provide assistance to provide security to witnesses and / or victims that must be carried out by LPSK or other institutions in accordance with the provisions of Law No. 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection Witness and Victim. Legal protection as a description and function of law is the concept where the law can provide justice, order, certainty, usefulness and peace. One of the legal pieces of evidence in the criminal justice process is expert statements. The role of experts in the trial is to provide information in accordance with their expertise in order to make light of a case. However, what is happening right now is that there are efforts to prosecute experts who have provided information in the resolution of criminal cases. The problem raised in this study is how the legal protection of experts who provide information in court.The research conducted is normative legal research. Sources and types of data obtained from secondary data obtained from various library studies and legislation, books, literature relating to the problem of this research.In the research results there are two main problems that can be concluded. First, in providing preventive legal protection regulations made to protect experts to avoid threats when providing information, when examining criminal cases, experts feel safe, without pressure from any party, and experts are also free to provide information before law enforcement officials without any elements. coercion. Second, protection regarding expert statements in the future needs to be reaffirmed in the relevant laws and provide legal certainty for an expert providing information in criminal cases.Suggestions in this paper so that the legal protection of experts in the examination of criminal cases runs well relating to the rights obtained more expanded, protection must also be given without having an expert ask for protection and also provide legal certaintyKeywords: Legal, Protection, Experts, Courts